REVIEW: UPAYA KONSERVASI TANAMAN AKUMULATOR UNTUK MEMINIMAL CEMARAN LOGAM BERAT DI LAHAN TAMBANG TIMAH, PULAU BANGKA - Mustikasari, Diah (Teknosains: Media Informasi Sains dan Teknologi, 2019)
Tin mining activities in Bangka Island have caused ecosystem damages including deforestation which has an impact on the loss of local flora and fauna, ecological imbalances, decreases in land and water quality, and heavy metal contamination such as Pb, Sn, Zn, Mn, Fe, Cr , Cu, Ni, Cd, and As. The post-mining ecosystem must be restored to restore its function as a life supporting system for the organisms in the ecosystem. This paper aimed to elaborate information related to the condition of post-mining land related to ecological damage and heavy metal contamination and the potential for the conservation efforts of bioaccumulator plants which can reduce heavy metal contamination and improve the quality of land functions. This paper was expected to be one of the references for making decisions on sustainable post-mining environmental management so that the land is habitable for the flora and fauna of the ecosystem. Some plants which have heavy metal accumulation potential are Calophyllum pulcherrimum, Cratoxylum formosum, Gluta velutina Blume, Gordonia excelsa Blume, Ilex cymosa Blume, Ixonanthes petiolaris Blume, Lithocarpus sp, Lophopetalum javanicum, Schima wallichii, Tristaniopsis whiteana, Acacia mangium, Enterolobium cyclocarpum, Gliricidia sepium, Delonix regia, dan Cassia siamea Lamk. The accumulator plants develop their mechanism such as rhizodegradation, phytostabilization, phytodegradation, phytoaccumulation/ phytoextraction, phytovolatilization, phytofiltration, dan phytodesalination.